Short-term detraining does not impair strength, speed, and power performance in elite young soccer players - Pereira, L. A.; Freitas, T. T.; Pivetti, B.; Alcaraz, P. E.; Jeffreys, I.; Loturco, I. (Sports, 2020)
This study aimed to examine the effects of short-term detraining on the strength, speed, and jump capacities of under-20 soccer players. Twenty-four elite under-20 soccer players from the same professional club were assessed pre and post 26 days of detraining. The measurements were performed in the following order: countermovement jump (CMJ); 10 m linear sprint velocity; and one-repetition maximum test (1RM) in the horizontal leg-press exercise. To analyze the differences between pre- and post-tests, a paired T-test was applied. The significance level was set as p < 0.05. Soccer players exhibited a significant increase in CMJ performance (p = 0.02) and no significant differences in 10 m sprint velocity and 1RM leg-press were found after the short-term training cessation (p = 0.61; p = 0.55, respectively). We demonstrated that a short-term detraining period was capable of promoting a significant increase in the vertical jump height without inducing negative effects on the strength and speed capabilities of elite under-20 soccer players. Practitioners and sport scientists should be aware of these findings to program more effective training strategies at the beginning of the subsequent training cycle